The appeal of the functional fitness MOT to older adults and health professionals in an outpatient setting: A mixed-method feasibility study - De Jong, Lex; Peters, A.; Gawler, S.; Chalmers, N.; Henderson, C.; Hooper, J.; Laventure, R.; McLean, L.; Skelton, D. (Dove Medical Press Ltd., 2018)
Purpose: To understand the views and perceptions regarding the Functional Fitness MOT (FFMOT), a battery of functional tests followed by a brief motivational interview, of both the older people undergoing it and the health professionals delivering it. Patients and methods: Physically inactive older adults (n=29) underwent the FFMOT and subsequently attended focus groups to share their perceptions of it and to discuss the barriers, motivators, health behavior change, and scope to improve physical activity (PA) levels. PA levels were recorded at baseline and again at 12 weeks together with a post-intervention questionnaire concerning behavior change. Participating physiotherapists and technical instructors were interviewed. Results: Most participants felt they had learned about their abilities and comparisons with their peers, had a change in perception about the importance of good balance and strength, and felt the FFMOT helped raise their awareness of local and self-directed physical activity opportunities. Most felt their awareness of the need for PA had not changed, but 25% of participants started a new organized PA opportunity. The health professionals perceived the FFMOT as being easy to administer, educating, and motivating for participants to increase their PA. Space, time, finances, and insecurity about having the necessary skills to conduct the FFMOTs were seen as barriers in implementing the FFMOT in daily practice. Conclusion: Over half of those offered the FFMOT accepted it, suggesting it is appealing. However, most participants felt they were already active enough and that their awareness of the need for PA had not changed. There were positive perceptions of the FFMOT from both professionals and older people, but both felt the FFMOT could be held in a community venue. The overall findings suggest that the FFMOT is feasible in the clinical setting, but its effectiveness has yet to be determined.